Checklist of cognitive contributions to diagnostic errors: a tool for clinician-educators - Naude, Jonathan Michael (Department of Medicine, 2019)
Background: Experienced clinician educators readily identify trainees with diagnostic reasoning difficulties but often lack training to diagnose and remediate errors. Taxonomies of cognitive causes of diagnostic errors can inform remediation, but clinician educators need simple tools to identify, record, report and provide feedback on these errors. A checklist may help achieve these goals. Objectives: To characterise the cognitive contributions to diagnostic errors (CCDEs), trainees make in patient encounters, with the view to develop training and remediation programmes for medical residents preparing for specialist examinations. Secondly, to determine examiners’ perceptions of a checklist in order to document and provide feedback on CCDEs to unsuccessful candidates and trainees making diagnostic errors in examinations, on ward rounds and during bedside teaching activities. Methods: Thirty examiners used a 17-item checklist to identify and record CCDEs made by medical residents failing patient encounters in a national specialist examination. A survey was used to explore examiners perceptions of the checklist to document and provide feedback on these errors. Results: Ninety-eight of 264 patient encounters were failed (37%). Ninety-four completed checklists documented 691 CCDEs (median of 7 per encounter). Cardiac (28.7%) and neurology patients (18.1%) constituted approximately half of the failed encounters. By category: data synthesis was more problematic than data gathering, faulty knowledge or data interpretation (35.2% vs. 25.8% vs. 21.9% vs. 17.1%); χ2=48.2, (p<0.0001 for all comparisons). The 'top five’ individual CCDEs were failure to elicit history and/or examination findings; poor knowledge of clinical features (illness scripts); case synthesis (putting the case together) and misinterpretation of clinical findings. History and physical examination-related errors accounted for 60% of the 'top 5’ CCDEs, Examination-related errors were more common than history-related errors (p<0.0001). The survey of the checklist was completed by all (30) examiners. Seventy-three percent finished the checklist in less than five minutes, describing it as comprehensive and easy to use. The majority (96.7%) thought the checklist could be a better way of providing structured feedback to unsuccessful candidates. Most examiners (93.3%) considered it a useful way of guiding bedside teaching for residents preparing for specialist examinations, and 76.7% thought it could improve feedback on CCDEs to unsuccessful candidates and guide remediation and training. Conclusion: A 17-item checklist identified three priority CCDEs which require focussed remediation and training in South African medical residency programmes: improving clinical skills, developing adequate illness scripts and 'putting a case together’. This does not require extensive pedagogic expertise but rather use of a simple tool to provide customised feedback, remediation and faculty support. We showed that the simple checklist used in this study helped clinician-educators/examiners without pedagogic expertise to diagnose and record CCDEs contributing to poor performance in high stakes examinations. Examiners endorsed the use of the checklist and its potential to improve feedback and training addressing CCDEs made by trainees at the bedside.